A child with Down Syndrome and Type 2 Diabetic Mellitus - Betti Bettavia Hartama Pardosi; Sianny Herawati; Ni Kadek Mulyantari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Down Syndrome (DS) is one of the common chromosomal disorders that raise mental retardation. It is known that DS patients have an autoimmune disorder affecting the endocrine and non-endocrine organs. It is a rare occurrence of type 2 Diabetes Mellitus (type 2 DM) disease in children with DS. Type 2 DM occurs due to impaired insulin secretion and excessive hepatic glucose production, unlike type 1 DM, caused by the destruction of íŸ-cells in autoimmune Langerhans. A 10-year-old girl patient was referred from Tabanan Hospital to Sanglah Hospital, Denpasar. Patients were admitted to the hospital with decreased consciousness, treated for four days, and observed in ICU for 2 days. Vomiting twice, no seizures, urinating normally. No significant past medical history was found. Physical examinations showed a typical Mongolian face, short neck, expanded occipital area, small eyes, and a mouth with a prominent tongue. Laboratory data revealed fasting blood glucose of 473 mg/dL and an HbA1C level of 12.6%. Urinalysis showed ketone 3+. The C-peptide test showed a reasonably good íŸ pancreas cell function. Down syndrome is associated with autoimmune diseases, including type 1 diabetes. The exact number of down syndrome cases with type 2 DM remains unknown; however, it was known that the case is infrequent.